An improved auxin-inducible degron system for fission yeast. Issue 1 (25th November 2021) - Zhang, Xiao-Ran; Zhao, Lei; Suo, Fang; Gao, Yadong; Wu, Qingcui; Qi, Xiangbing; Du, Li-Lin
Abstract: Conditional degron technologies, which allow a protein of interest to be degraded in an inducible manner, are important tools for biological research, and are especially useful for creating conditional loss-of-function mutants of essential genes. The auxin-inducible degron (AID) technology, which utilizes plant auxin signaling components to control protein degradation in nonplant species, is a widely used small-molecular-controlled degradation method in yeasts and animals. However, the currently available AID systems still have room for further optimization. Here, we have improved the AID system for the fission yeast Schizosaccharomyces pombe by optimizing all three components: the AID degron, the small-molecule inducer, and the inducer-responsive F-box protein. We chose a 36-amino-acid sequence of the Arabidopsis IAA17 protein as the degron and employed three tandem copies of it to enhance efficiency. To minimize undesirable side effects of the inducer, we adopted a bulky analog of auxin, 5-adamantyl-IAA, and paired it with the F-box protein OsTIR1 that harbors a mutation (F74A) at the auxin-binding pocket. 5-adamantyl-IAA, when utilized with OsTIR1-F74A, is effective at concentrations thousands of times lower than auxin used in combination with wild-type OsTIR1. We tested our improved AID system on 10 essential genes and achieved inducible lethality for all of them, including ones that could not be effectively inactivated using a previously published AID system. Our improved AID system should facilitate the construction of conditional loss-of-function mutants in fission yeast.